Estudo comportamental e neuroquímico do β cariofileno no modelo de epilepitogenese induzida por pilocarpina em camundongos - Rosa, Lucas Diogo (2020)
Epilepsy is a worldwide neurological disorder that affects different age groups and impairs the quality of life of individuals. Available therapies, in some cases, do not have a satisfactory therapeutic response or have many side effects. Thus, the development of new antiepileptic agents capable of modifying the pathogenesis of epilepsy is still urgently needed. Currently, researches indicate as medicinal alternatives, drugs of plant origin because they have low side effects and proven efficacy. In this context, the beta-caryophyllene compound is a plausible alternative for studies, and this compound may be a future alternative for the treatment of epileptic seizures, since many biological properties have already been described using this compound in several experimental models. Therefore, the aim of the study was to evaluate the effect of beta-caryophyllene (BCF) in a model of pilocarpine-induced epileptogenesis in mice. This study was submitted to the Ethics Committee on the Use of Animals of the Federal University of Ceará, Campus Sobral and approved under protocol number 08/2018. Young male Swiss mice weighing between (20-25g) were divided into two groups, namely: epileptic (EG) and non-epileptic (GNE). The EG was submitted to the epileptogenesis induction protocol by pilocarpine. For this group, the animals were previously treated with methylscopolamine (1mg/kg, ip), and then received pilocarpine in divided doses of 100 mg/kg, ip, not exceeding four administrations (400mg/kg) with intervals of 20 minutes, for the induction of status epilepticus (SE). After 2 hours of the last administration of pilocarpine the SE was aborted by the administration of diazepam (10mg/kg, i.p). The GNE followed the same protocol, but pilocarpine was replaced by saline solution (NaCl 0.9%), indicating the absence of SE. After 24 hours, both groups started treatment with BCF at concentrations of (50 mg/kg or 100mg/kg, v.o) or 0.9% saline for 14 days. On the 12th, 13th and 14th days of treatment, behavioral tests were performed (open field, object recognition and rotarod). At the end of the tests, on the fourteenth day of treatment and 60 minutes after the last administration of BCF, the animals were euthanized and the brain areas hippocampus (HC), prefrontal cortex (CPF) and striatum (CPE) were dissected for neurochemical assays to investigate lipid peroxidation (TBARS), reduced glutathione (GSH) and nitrite/nitrate levels. The results were analyzed by analysis of variance (ANOVA), followed by Tukey's multiple comparisons test. A significance level of 95% (p<0.05) was applied to all statistical tests. In the rotarod test, the BCF 50 mg/kg and 100 mg/kg GNE concentrations increased the fall latency time (850% and 1073%, respectively) compared to the saline groups. Regarding the number of falls, 100 mg/kg of βCF in GNE decreased 73.36% compared to saline. In EG, 50 and 100 mg/kg of βCF reduced the number of falls by 64.78% and 56.45%, respectively. longer in the stem (26.24% and 28.99%, respectively) compared to the saline group. As for neurochemical analyses, GSH significantly increased in GE at the dose 100mg/kg in HC (11.9%) compared to the saline group. In GNE, there was an increase in the dose of 50 mg/kg in HC (83.72%) when compared to saline. The analysis of the levels of nitrite and nitrate, only the dose of 50 mg/kg in the striatum of the experimental group GE showed a statistical difference, increasing 162% compared to the saline group GE. Regarding lipid peroxidation, there was only a significant difference in relation to the GNE experimental group, where the two doses tested (50 mg/kg and 100 mg/kg) showed a significant decrease in HC (36.2% and 29.73%, respectively) and CPF (30.42% and 21.26%, respectively). Thus, it is possible to observe that the BCF improves the motor condition and decreases the oxidative stress of animals that were submitted to SE at the concentrations tested, being able to reduce the number of falls, increasing the fall latency and time spent on the rotarod beyond of increasing GSH levels and decreasing TBARS levels, showing possible neuroprotective activity.